Stefanos Lazaridis - Volanakis, Adonis (My University, 2026)
Installation for hosting an archive exhibition, Production: Greek National Opera, in collaboration with the National Bank of Greece Cultural Foundation (MIET), and the National Library of Greece, Stavros Niarchos Foundation Cultural Center (SNFCC), Athens, Greece.